Quality Characteristics of Robusta Coffee (Coffea Canephora) from Tebat Pulau village Rejang Lebong Regency with the Variation of Roasting Time - Arthia Isah Hartanti Lumbanraja; Budiyanto Budiyanto; Yuwana Yuwana (AGRITROPICA : Journal of Agricultural Sciences, 2023)
Tebat Pulau Village is a formerly protected forest area that has become a community social forest processed and planted with robusta coffee. Robusta coffee from the Tebat Pulau Village Farmers Group is of good quality because it is in great demand and attracts the attention of large buyers. However, the quality profile, the roasted coffee criteria, and the preferred quality of the brewed coffee are not yet known. Therefore, this research was conducted to determine the quality profile of rice coffee, the physical and chemical characteristics of ground coffee and the brewing quality of robusta coffee during roasting time. The experimental design used was Completely Randomized Design with one factor. The factor tested was roasting time (P), which consisted of 4 treatment levels, namely P1:10 minutes, P 2:11 minutes, P3:12 minutes, P4:13 minutes with roaster temperature 200°C and bean temperature 107°C. The research was carried out with three repetitions to produce 12 experimental units. The results showed that the coffee from the Tebat Pulau Village Farmer Group had quite large coffee beans with a water content value of 9.00%, had quite a lot of lanang (peaberry bean) coffee beans, and had a total defect value of 13.83. Ground coffee samples with a long roasting time significantly affected water content, color, ash content, coffee essence, and caffeine content. The best-brewed coffee quality was obtained at 12 minutes of roasting time with a final score of 8.50, included in the "fine" category.